CAS Wavelet Based Numerical Technique for the Solution of Dusty Tangent Hyperbolic Fluid Flow with Magnetic Dipole Effect, Quadratic Convection and Entropy Generation - S.C. Shiralashetti; Priyanka Kulkarni; Savita Hanaji (Journal of Applied and Computational Mechanics)
This paper presents the CAS wavelet based numerical technique for the solution of non-linear system of differential equations arising in the analysis of an unsteady dusty tangent hyperbolic fluid flow over a stretching sheet through porous medium with magnetic dipole effect, quadratic convection, non-linear radiation, convective boundary and entropy generation. Initially, the proposed method is implemented on the test problem having the exact solution. The results obtained are very close to the exact solution in comparison with the Runge-Kutta Fehlberg 4th – 5th order method. The considered dusty fluid problem is solved by using the proposed technique. The solutions obtained for certain fixed parameters are compared and found to be coinciding with the solutions given in the literature. The comparisons and convergence analysis validate the method. The flow behaviour of dusty tangent hyperbolic fluid is analysed and the impact of various factors on the velocity and thermal profile of the fluid are studied. It is inferred that the Weissenberg number, power law index and Ferro-hydrodynamic interaction parameter declines the velocity and improves the temperature. Opposite behaviour is observed for mixed convection and quadratic convection parameters. The temperature increases for the Biot number. The Weissenberg number declines the entropy generation and enhances the Bejan number. A reverse trend is noticed for Brinkman number. CAS wavelet based numerical technique is simple, reliable, highly accurate, efficient and effective tool to solve the non-linear system of differential equations arising in dusty fluid flow problems.